Factors Influencing Consumers’ Purchasing Decisions Towards Pomelo Fruits (Citrus grandis) in Johor, Malaysia - Siti Fatimah Binti Misman; Nurul Aisyah Binti Mohd Suhaimi; Afnani Binti Alwi (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Pomelo (Citrus grandis or Citrus maxima) is a tropical fruit from Rutaceae family has grown in Malaysia. These natural, non-hybrid citrus fruits originated from Southeast Asia and widely grown in Indonesia, China and Thailand (Morton, 1987; Scora, 1975). Commonly known as Limau Kepala Besar, Limau Bali (pomelo), Limau Tambun and Limau Besar Ledang, this fruit have four famous varieties such as Varieties PO51 (Shanting), Varieties PO52 (Tambun), Varieties PO55 (Limau Besar, Ledang) and Varieties PO56 (Melomas Variety) which can be found in the local and global markets. The aim of this research is to study the characteristics behind every purchasing decision through personal, socio-cultural and psychological factors of consumer. Data were collected using online questionnaire which a total of 100 forms were distributed around Johor, Malaysia. The data were analyzed to identify the relationship between respondent profiles and identify the most influential factors that show the relationship associations with consumer purchasing decisions on pomelo fruits. The results showed that personal, socio-cultural and psychological factors have influenced consumers’ decision-making process when buying the pomelo fruits.